Conference Guest Editorial Board (International Journal of Physiotherapy, 2025)
International Conference on Advances in Physiotherapy (ICAP) 2.0The highly anticipated International Conference on Advances in Physiotherapy (ICAP) 2.0 was successfully held on November 9-10, 2024, by the Department of Physiotherapy at the University of Engineering and Management (UEM), Jaipur.This premier event brought together renowned experts, researchers, and practitioners in physiotherapy to share cutting-edge knowledge, innovative techniques, and best practices.Over two days, delegates engaged in stimulating discussions, hands-on workshops, and keynote presentations that explored the latest advancements in physiotherapy research, education, and clinical practice.Over 150 abstracts were submitted to the ICAP 2.0, out of which 50 were selected to present at the conference.ICAP 2.0 provided a dynamic platform for networking, collaboration, and professional growth, cementing its position as a flagship event in the physiotherapy community.